2016
DOI: 10.1111/bcpt.12535
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the Sedative Effects of Propofol in Patients undergoing Spinal Anaesthesia: A Pharmacodynamic Analysis

Abstract: Sedation can increase patient comfort during spinal anaesthesia. Understanding the relationship between the propofol effect-site concentration (Ce) and patient sedation level could help clinicians achieve the desired sedation level with minimal side effects. We aimed to model the relationship between the propofol Ce and adequate and deep sedation and also incorporate covariates. Thirty patients scheduled for orthopaedic surgery received spinal anaesthesia with 0.5% bupivacaine. Propofol was administered via an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This is consistent with Schnider et al [19] who observed increasing sensitivity to propofol in elderly patients for loss of consciousness. Both age and level of spinal anesthesia have been reported to modify sedation scores [28]. In the current study, age is the more important modifying factor of OAA/S as the overall level of spinal anesthesia demonstrated little variation among participants (T9 ± 1.5 dermatomes).…”
Section: Discussionmentioning
confidence: 50%
“…This is consistent with Schnider et al [19] who observed increasing sensitivity to propofol in elderly patients for loss of consciousness. Both age and level of spinal anesthesia have been reported to modify sedation scores [28]. In the current study, age is the more important modifying factor of OAA/S as the overall level of spinal anesthesia demonstrated little variation among participants (T9 ± 1.5 dermatomes).…”
Section: Discussionmentioning
confidence: 50%
“…Since spinal anesthesia can be a stressful experience, premedication was administered to some patients to facilitate their comfort during anesthesia performance. Therefore intraoperative sedation is a common practice [15,16]. After the spinal block procedure, the upper level of the sensory block was evaluated using the cold test, and motor blockade was assessed with a modified Bromage score [17].…”
Section: Methodsmentioning
confidence: 99%